Interactions between externally forced climate signals from sunspot peaks and the internally generated Pacific Decadal and North Atlantic Oscillations. Issue 1 (15th January 2014) - van, Harry; Meehl, Gerald A.
Abstract When the Pacific Decadal Oscillation is in phase with the 11 year sunspot cycle, there are positive sea level pressure (SLP) anomalies in the Gulf of Alaska, nearly no anomalous zonal SLP gradient across the equatorial Pacific, and a mix of small positive and negative sea surface temperature (SST) anomalies there. When the two indices are out of phase, positive SLP anomalies extend farther south in the Gulf of Alaska and west into eastern Russia, with a strengthened anomalous zonal equatorial Pacific SLP gradient and larger magnitude and more extensive negative SST anomalies along the equatorial Pacific. In the North Atlantic, when the North Atlantic Oscillation (NAO) is in phase with the sunspot peaks, there is an intensified positive NAO SLP pattern. When the NAO is out of phase with the peaks, there is the opposite pattern (negative NAO). The relationships are physically consistent with previously identified processes and mechanisms and point the way to further research.